2021
DOI: 10.11594/ijmaber.02.07.04
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Takers of the Qualifying Examinations as Part of the Accountancy Program Retention Policy: The Case of a University in Central Luzon Philippines

Abstract: This research was carried out to assess the qualifying examinations being administered by a school’s department for a of university in Central Luzon, Philippines for the Incoming Second Year, Third Year and Fifth Year BS Accountancy Students. Using the physical and administrative factors are from Aiken et al. (2008), and the Psychological Testing and Assessment, and University of Waterloo’s Center for Excellence (2016), when Preparing Tests and Exams are the guidelines for qualitative factors of exams revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…One of the most prevalent problems of accountancy students is passing the battery examinations. Hence, the majority of them suggested that the department intensify the conduct of tutorial and review classes [20][21]. Also, Salcedo, et al (2021) found out that students' attendance at tutorial classes, the commitment to majoring in Accounting, and a demonstrated interest in Accounting correlate positively and significantly with academic performance.…”
Section: Suggestions Of Students To Increase Retention Rates and Impr...mentioning
confidence: 99%
“…One of the most prevalent problems of accountancy students is passing the battery examinations. Hence, the majority of them suggested that the department intensify the conduct of tutorial and review classes [20][21]. Also, Salcedo, et al (2021) found out that students' attendance at tutorial classes, the commitment to majoring in Accounting, and a demonstrated interest in Accounting correlate positively and significantly with academic performance.…”
Section: Suggestions Of Students To Increase Retention Rates and Impr...mentioning
confidence: 99%